Mirror images : new reflections on teacher leadership - Reason, Casey S. (Corwin Press, 2011)
"Teacher Leadership 2.0 is a step-by-step discussion and description of how and why to foster teacher leadership in schools. Unlike top-down delivered leadership, this book will seek to empower teachers throughout schools to create and grow in leadership roles. This topic has gained traction in district and school level discussions and has become a key topic at teacher and principal conferences in the last few years. There are five conceptual must-haves that are essential in promoting teacher leadership in schools today. Must-Have #1: Why Top Down Change Is Less Effective Today Than Ever Must-Have #2: Teacher Leadership in Schools Is a Force Not a Position Must-Have #3: Why We Don't See Teachers as Leaders (Bad Images of Teachers) Must-Have #4: Leadership, Learning, and Change Are One Must-Have #5: Teacher Leadership: A New Definition"-- Provided by publisher.